KULIT COWEBA (Inocarpus fagifer Fosberg) SEBAGAI ANTIDIABETES ALAMI ASAL PAPUA - Maelissa, Yanty Mega Puspita; Praptiwi, Nitya dewi; Ofias, Jefri Laban; Darwis, Darwis (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Coweba (Inocarpus fagifer Fosberg) has traditionally been used to treat diabetes in ethnic Isirawa, Sarmi, Papua. The purpose of this study was to extract and determine the antidiabetic active compound content of polar and non-polar extracts of skin Coweba (Inocarpus fagifer Fosberg) as the basis for the development of natural antidiabetic drugs based on local resources. The method used in this study, namely, maceration with methanol solvent, fractionation, screening phytochemical, antidiabetic activity test É-glucosidase inhibition. Identification of chemical constituents in the extract contains compounds include classes of secondary metabolites: alkaloids, flavonoids, triterpenoids or steroids, saponins and tannins. The results showed that the methanol extract of red that was obtained with yield of 6.11% and a strong positive contains flavonoids and alkaloids. The results of the analysis of the methanol extract using FTIR, indicating the presence of an absorption band -OH, C = O, and C = C aromatic, characteristic for the uptake of flavonoid compounds. Test of Î±-glucosidase inhibitory activity, indicating that the methanol extract of the bark has coweba has the capability of the enzyme alpha glucosidaseÂ inhibitionÂ thatÂ is equalÂ to 75.86% with IC50 value of 0.814 ppm. This indicates that the plants Coweba very potential to be developed as a raw material of natural herbal antidiabetic drugs.Keywords: Â Coweba, antidiabetic, Î±-glucosidase, phytochemical